Comparative study of metakaolin, pumice powder and silica fume in producing treated sustainable recycled coarse aggregate concrete by adopting two-stage mixing - Gaurav Chand; Abhishek Kumar; Shobha Ram (Cleaner Engineering and Technology, 2022)
In the present study, SCMs like metakaolin, pumice powder and silica fume are used as partial replacement with cement by coating the surface of RCA, to fill the gaps and pores of adhered mortar present on it. Prior to this step, the RCA is treated with 0.1 M Hydrocloric (HCl) acid solution, in order to weaken the adhered mortar present on its surface. The results obtained, under mechanical properties investigation, show that the compressive strength of treated recycled aggregate concrete (RAC), produced using metakaolin, pumice powder and silica fumes, attains 34.46%, 31.81% and 50.75% higher strength compared to the untreated RAC specimen. Moreover, the treated RAC, produced using silica fume, attains 10.86% of significant higher strength compared to the control mix specimen. The improved strength obtained in silica fume specimen is attributed to the development of stronger interfacial transition zone (ITZ) and the formation of strength inducing compounds like calcium silicate hydrate (C–S–H), validated under microstructural investigation performed by scattered electron microscopy (SEM).